Attachment and brooding rumination during children's transition to adolescence: the moderating role of effortful control - Lindblom Jallu; Bosmans Guy (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Brooding rumination is a maladaptive form of emotion regulation and confers a risk for psychopathology. Insecure attachment and low cognitive self-regulation are important antecedents of brooding. Yet, little is known about the developmental interplay between these two systems. Thus, we tested how children's attachment and cognitive self-regulation, conceptualized as effortful control (EC), interact to predict brooding. The participants in the three-wave longitudinal study were n = 157 children (10 to 14 years) and their mothers. Children reported their attachment and brooding, and mothers reported children's EC. Results showed that children with low avoidance received benefit from high EC to decrease brooding, whereas children with high anxiety brooded irrespective of EC. Thus, high EC may foster constructive emotion regulation among securely attached children, whereas the beneficial effects of high EC on emotional functioning seem to be overridden by insecurity. The functional role of cognitive self-regulation on different attachment strategies is discussed.